FRI0418 Case-mix in a rheumatology outpatient department of a london teaching hospital. (23rd January 2014) - Kirkpatrick, B.; Ludwig, D.; Pyne, D.; Kelly, S.
Abstract : Background: As a result of mounting financial pressures in the UK National Health Service, Rheumatology outpatient departments are under pressure from commissioning groups to adhere to pre-defined "new-to-follow-up" (N:FU) patient ratios. However, with many rheumatology patients requiring regular follow-up due to the nature of both their chronic condition and their treatment it appears that low new-to-follow-up target ratios could be difficult to meet. Objectives: In the East End of London a target N:FU ratio of 1:4 has recently been commissioned. We aimed to study the patient case-mix in the Rheumatology outpatient department at The Royal London Hospital in East London to determine the feasibility of complying with this target. Methods: Information was collected retrospectively over a 4 week period in November 2011 from all rheumatology consultant - led clinic lists at the Royal London Hospital. Clinic letters were used to determine diagnosis and treatment. Results: 1148 outpatients were seen over the 4 week period. Mean patient age was 51.The overall N:FU ratio was 7.2. The majority of patients had chronic conditions: 42% (n=478) had Inflammatory Arthritis (IA) of which rheumatoid arthritis was the commonest (21%, n=238) followed by psoriatic arthritis (7%, n=86), then ankylosing spondylitis (5%, n=60); 14% (n=162) had a connective tissue disease (CTD) of which lupus was the commonest (7%, n=81). Within the IA and CTD groups 71% (n=339) and 63% (n=101) respectively were on immunosuppressant drugs which required specialist follow up. The remaining patients had soft tissue disorders, which included back pain (5%, n=61), metabolic bone disorders (6%, n=71), osteoarthritis (9%, n=104), unknown (6%, n=73) and other (7%, n=85) e.g. sarcoidosis and chronic pain syndrome. Conclusions: Around 60% of the outpatient work-load of the Rheumatology Department is dealing with IA or CTDs - these are patients with chronic diseases, the majority of whom are on specialist drugs, and who cannot therefore be easily discharged back into the community. Soft tissue disorders and osteoarthritis which are mainly managed in the community make up a much smaller percentage of hospital work. We would therefore urge commissioners that in making decisions regarding appropriate N:FU ratios for outpatients consideration be taken of the current case-mix in rheumatology units. Disclosure of Interest: None Declared